(untitled) (Journal of Enam Medical College, 2019)
Background: Gunshot injuries result from the effect of a bullet or projectiles emanating from the use of firearms. Firearm injuries are associated with substantial emotional, physical and financial burden causing an enormous human toll and imposing huge costs on the society. Abdominal injuries are associated with a high incidence of internal injury. These injuries are increasingly seen in many developing countries, which have been attributed to communal and ethnic clashes, political violence and armed robberies. Objective: The objective of this study was to determine the overall outcome of hollow viscus injury following gunshot on the basis of time duration of presentation and amount of blood loss at the time of presentation. Materials and Methods: This observational study was conducted at casualty department of Dhaka Medical College & Hospital over a period of one year from October 2014 to October 2015. All admitted patients with hollow viscus injury due to gun shot at casualty department of DMCH were included in this study by selective sampling technique. The main outcome variables were postoperative wound infection, anastomotic leakage, number of deaths and prolonged hospital stays. Data processing and analysis were done using SPSS 17.0. Results: There were total 76 patients with hollow viscus injury following gunshot during the period under review. All were male patients with mean age 31.13 years. Peak incidence occurred within age group 41–60 (52.6%). The most commonly injured organs were the small bowel in 34 patients (44.7%). Thirty (90.9%) patients presented within three hours of the event (p=0.001). Among six patients who died, 5 (83.8%) presented 10 hours after the event (p=0.001). Among 20 patients, 18 (90%) remained hospitalized more than 15 days, who presented within 4–6 hours of the event (p=0.001). In 29 out of 33 patients (87.9%) who did not suffer from any complications encountered only less than 15% of blood loss at the time of presentation (p=0.001). Among 15 patients who suffered from postoperative wound infection nine patients (60%) lost 30–40% of blood at the time of presentation (p=0.011). Conclusion: Outcome of the patients with hollow viscus injury following gunshot were found to be related to the time taken to reach the casualty department from the place of event and the amount of blood loss at the time of presentation. J Enam Med Col 2019; 9(2): 110-115